2022
DOI: 10.3846/cs.2022.14264
|View full text |Cite
|
Sign up to set email alerts
|

Creative Processes and Emotions in Covid-19 Pandemic

Abstract: The objective was to analyse, from the perspective of the participants, creative processes developed in isolation and social distancing by COVID-19 pandemic. The main interest was to study transformations in daily, family and work life, focusing on the creation of new practices and projects. Likewise, it was relevant to study emotions, obstacles and difficulties perceived by the participants. The study was qualitative, the participants (N = 25) were selected by non-probabilistic convenience sampling. All the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
2
1
0
Order By: Relevance
“…This is demonstrated in broadening the entrepreneurs' thoughts to experiment with new recipes, learn new skills, and foster individual resilience to start a new business despite their previous negative business experience (Participant 1) or to innovate in different ways to keep their business going (Participant 3). Furthermore, these findings are also in accordance with previous studies that reported that people during lockdown were creating novel and creative activities at home [78]. Among the creative activities mentioned were: experimenting with new recipes; growing vegetables; taking care of children and devising games; rearranging the schedule and space at home; inventing new forms of remote work, fostering practices of solidarity; building exercise equipment; and coming up with new school activities for the children [77].…”
Section: Entrepreneurship Motivations Pre-and During Covid-19 Pandemicsupporting
confidence: 90%
See 2 more Smart Citations
“…This is demonstrated in broadening the entrepreneurs' thoughts to experiment with new recipes, learn new skills, and foster individual resilience to start a new business despite their previous negative business experience (Participant 1) or to innovate in different ways to keep their business going (Participant 3). Furthermore, these findings are also in accordance with previous studies that reported that people during lockdown were creating novel and creative activities at home [78]. Among the creative activities mentioned were: experimenting with new recipes; growing vegetables; taking care of children and devising games; rearranging the schedule and space at home; inventing new forms of remote work, fostering practices of solidarity; building exercise equipment; and coming up with new school activities for the children [77].…”
Section: Entrepreneurship Motivations Pre-and During Covid-19 Pandemicsupporting
confidence: 90%
“…According to these participants, viewing the COVID-19 pandemic through a positive lens allowed them to focus more on self-improvement and creativity by staying at home and away from external noise and disruptions. The aforementioned findings are consistent with other research demonstrating how having positive emotions during the isolating pandemic lockdown enabled individuals to realize their latent creativity [78,79]. Participant 5 was very proud of her name and the success of her business, a new positive emotion.…”
Section: Entrepreneurship Motivations Pre-and During Covid-19 Pandemicsupporting
confidence: 89%
See 1 more Smart Citation
“…En concordancia con estudios anteriores (Elisondo, 2021(Elisondo, , 2022Elisondo y Melgar, 2021;Karwowski et al, 2021), se observó que cocinar fue la actividad mencionada por la mayoría de los participantes cuando se les consultó en relación a acciones creativas Los análisis indicaron menores niveles de estrés en padres con mejores autopercepciones creativas y con estrategias de afrontamiento positivas. Los resultados del estudio de Lades et al (2020) también indicaron que pasar tiempo con los niños contribuyó al bienestar emocional de los padres durante el confinamiento.…”
Section: Discussionunclassified
“…En la investigación realizada en abril de 2020, los análisis mostraron emociones positivas vinculadas a la ejecución de actividades creativas durante el confinamiento (Elisondo y Melgar, 2021). Los resultados del estudio llevado a cabo en septiembre de 2020 indican emociones positivas asociadas al desarrollo de nuevos emprendimientos y la consolidación de hábitos saludables y sustentables (Elisondo, 2021(Elisondo, , 2022. En una línea argumentativa similar, Tang et al…”
Section: Introductionunclassified